Mechanistic study of the hydrodeoxygenation of lignin-derived oxygenates on a CoPt bimetallic catalyst: reaction of anisole on Co-modified Pt(111). (20th November 2018) - Shi, Daming; Vohs, John M
Abstract: Temperature programmed desorption and high-resolution electron energy loss spectroscopy were used to characterize the adsorption and reaction of anisole (C6 H5 –OCH3 ) on Pt(111) and Co-decorated Pt(111) surfaces. On both surfaces anisole was found to undergo O–CH3 bond cleavage to form an oxocyclohexadienyl-structured intermediate (C6 H6 O) which bonds to the surface in a η 5 - π configuration. Interaction of the O atom in this intermediate with Co adatoms was found to facilitate selective cleavage of the C–O bond to produce adsorbed benzene or phenyl groups. In parallel with this pathway, unselective decomposition of adsorbed anisole was also found to occur. The results obtained in this study along with those previously reported for the reaction of anisole on Zn-decorated Pt(111) surfaces provide further insight into how the addition of a second more oxyphilic metal to Pt affects surface reaction pathways and the hydrodeoxygenation selectivity of lignin-derived aromatic oxygenates.